Ritmo, affetto, senso. Ecologia dell’interazione e complessità sociale - Bondì, Antonino (Rivista Italiana di Filosofia del Linguaggio, 2020)
In this paper I will examine the notions of rhythm and affect, to evaluate their theoretical depth in the framework of an expressive and morphodynamic theory of semiolinguistic action. At first I intend to argue that rhythm and affect are conceptual tools useful to restore the complexity of semiolinguistic interactions and coordination and, to do so, I will focus on two different disciplinary areas. On the one hand I will resume research from developmental psychology and Infant Research, where rhythm is an indispensable dimension to define the intensive structure and the dynamic gait of the dialogic intersubjectivity. On the other hand, I will examine some implications of the concept of affect, today at the centre of the debate in cognitive anthropology and media studies. Affect, in these contexts, seems to have as much to do with the invoice of things as with the emotional dimensions and relational forces that structure the field of experience, determining its forms of cultural codification and social sharing.